Effect of non-ideal mixture on flame-spray interaction in counterflow n-heptane/ethanol flames - Hu, Yong; Gutheil, Eva; Jiang, Yong; Kurose, Ryoichi (Proceedings of the Combustion Institute, 2024)
This work presents a numerical study of bi-component n-heptane/ethanol spray flames in a counterflow to improve the understanding of the effect of non-ideal mixtures on the flame-spray interaction. The simulations of this spray configuration allow for the detailed examination of the real fluid behavior and its influence on gas-phase combustion kinetics for a wide range of relevant parameters, i.e., droplet composition, size, and gas strain rate. The results reveal that due to the large real activity coefficient of n-heptane and the resulting selective evaporation of the heavier component, the burning characteristics of the spray with a high initial ethanol content do not differ if non-ideal mixture is considered. Conversely, the flame structure with a low ethanol content is substantially different, and displacement of the flame towards the spray side of the configuration is found. A multiple reaction zone, displaying both partially-premixed and diffusion flames, exists, which is overestimated spatially if the fluid is assumed ideal. In general, the ideal prediction of real fluid would misinterpret the composition evaporation order, prolonging the droplet lifetime and consequently, enhancing the flame-spray interaction locally, which results in a lower flame temperature. A parameter characterizing the multicomponent droplet penetration is introduced, which highlights the appreciable non-ideal effects that vary with droplet size and composition, and most importantly, further demonstrates the necessity of considering the real fluid properties in design of next-generation engines with blended fuels.
Gesehen am 16.12.2024